Characterization of spent Purolite A530E resin with implications for long-term radioactive contaminant removal. Issue 5 (October 2020) - Levitskaia, Tatiana G.; Campbell, Emily L.; Hall, Gabriel B.; Chatterjee, Sayandev; Boglaienko, Daria; Reilly, Dallas D.; Carlson, Mark A.
Abstract: Direct removal of pertechnetate anion (TcO4 − ) from subsurface contaminated groundwater plumes at legacy nuclear weapons production sites, is an effective remediation strategy to prevent their spread to adjacent aquifers. However, it is also challenging because TcO4 − is a trace component in the contaminated groundwater, which typically contains a large excess of other anionic constituents, such nitrate, sulfate, chloride and others. Direct removal can be achieved through ion exchange treatment using Purolite A530E resin, which has been evaluated under laboratory conditions, but many questions regarding its long-term operational performance remain. To address this need, here we report comprehensive characterization of the spent Purolite A530E resin which processed over 5.38 × 10 9 L of contaminated groundwater and successfully removed about 3.78 Ci of technetium-99 during four years of operation at the 200 West Pump & Treat facility at the US DOE Hanford site. However, this TcO4 − loading constitutes only about 0.034 % of the theoretical capacity of the resin, which nearly fully loaded with nitrate and sulfate at the respective 79 and 6% of the resin capacity. Small quantity of iodine-127/129 was also retained by the resin. Mechanisms of competing anions sorption were investigated using pristine Purolite A530E resin, which exhibited highly efficient uptake of iodide and only moderate affinity for iodate. Sorption isotherms for both iodine anions and nitrate obeyed the Freundlich model. Selectivity trend observed for the pristine Purolite A530E resin followed the decrease in the Gibbs free energy of anion hydration allowing for the prediction of its relative affinity for different anions present in the influent streams.